IMPLEMENTASI KEBIJAKAN BANTUAN SOSIAL TUNAI (BST) PANDEMI COVID-19 DI KABUPATEN INDRAGIRI HULU TAHUN 2020 - Lina Listiana; Sofyan Hadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The implication of the impact of Covid-19 is the decline in economic growth including Indragiri Hulu Regency in 2020 for non-natural disaster emergencies, the Indragiri Hulu Regency Government distributes Cash Social Assistance (CSA), Cash Social Assistance (CSA) in Indragiri Hulu Regency only in 2020 while other districts are still distributing Cash Social Assistance (CSA) until 2021, of course in this case it is related to the implementation of policies that affect it.This research is to find out how the implementation of the Covid-19 pandemic Cash Social Assistance (CSA) policy in Indragiri Hulu Regency in 2020 and to find out the factors that influence the implementation of the Covid-19 pandemic Cash Social Assistance (CSA) policy in Indragiri Hulu Regency. This study uses a qualitative approach with a descriptive method. The types of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation.The results of this study are that the implementation of the Covid-19 pandemic Cash Social Assistance (CSA) policy in Indragiri Hulu Regency in 2020 is not in accordance with the Indragiri Hulu Regent Regulation Number 25 of 2020 which should have been implemented effectively in its distribution to be ineffective because there is a problem, namely Invalid data on Cash Social Assistance (CSA) recipients, and incorrectly targeted Cash Social Assistance (CSA) recipients. The factors that influence the implementation of the Covid-19 pandemic Cash Social Assistance (CSA) policy in Indragiri Hulu Regency in 2020 are poor communication and coordination between the Regional Government and the Village Government, Inadequate Resources due to lack of experts, Inadequate disposition effective, and a complicated bureaucratic structure. Keywords: Communication, Resources, Disposition, Bureaucratic Structure.